Trajectory Analysis and Risk Evaluation of Dangerous Rock Mass Instability of an Overhang Slope, Southwest of China - Wen-lian Liu; Jia-xing Dong; Han-hua Xu; Su-gang Sui; Run-xue Yang; Lun-shun Zhou (Advances in Civil Engineering)
Analysis of the movement trajectory and risk assessment of the high-slope dangerous rock mass collapse are of great significance for preventing and controlling the geological disasters of collapse. This study firstly takes the dangerous rock mass of the high slope in Pu’erdu Town, Yanjin County, Zhaotong City, Yunnan Province, as the research object, calculates and analyzes the trajectory of collapse movement of several groups of dangerous rock mass with great threat, and RocFall are used to carry out numerical simulation analysis and verification. Secondly, the risk and vulnerability of the dangerous rock mass in the study area are analyzed, and the risk evaluation is carried out through the risk evaluation matrix to clearly define the risk level. Results show that if the dangerous rock mass collapses, the horizontal movement distance was approximately 53–88 m, and the maximum bounce height of the platform was approximately 3–18 m, which will seriously threaten the life and property safety of residents. There is little difference between the simulation of the collapse of dangerous rock mass by RocFall software and the calculation result of the formula. Although RocFall software is more intuitive and can be directly compared with charts, software cannot completely simulate the actual situation, and it is only suggested as a reference from design rather than a basis of design. The result of risk evaluation shows that there are 2 high-risk dangerous rocks, 3 medium-risk dangerous rocks, and 1 low-risk dangerous rock in this area. It is suggested that a reasonable and scientific engineering treatment scheme should be put forward as soon as possible in combination with the collapse trajectory of the collapsing movement.